An Overview of Curriculum Requirements for Developing Key Competencies in Preschool Learners in English Lessons - Maftuna Tojiakhmedova (Indonesian Journal Publisher, 2025)
This article explores the curriculum requirements for the development of core (key) competencies in preschool learners through English language instruction. Rooted in the competency-based approach of Uzbekistan’s State Preschool Education Curriculum, the article outlines the nature and significance of key competencies in early childhood education, particularly within English language classes. It examines the theoretical foundations of communicative, social, personal, cognitive, and creative competencies, and provides examples of classroom practices aimed at nurturing these skills in children aged 6–7. The integration of these competencies is essential for ensuring children’s holistic development and smooth transition into primary education